Rhodium-Catalyzed Regioselective C7-Functionalization of Indole Derivatives with Acrylates by Using an N-Imino Directing Group - Xu, Lanting; Tan, Lushi; Ma, Dawei (Synlett, 2017)
An efficient rhodium-catalyzed method for C–H olefination at the C7 position of indoles has been developed. The N-imino directing group was shown to be crucial for high regioselectivity and reactivity of the metal catalyst. The utility of this protocol was further demonstrated through a concise, four-step synthesis of pyroquilon from indole.
Keywords: indoles; C7 regioselectivity; C–H activation; rhodium; olefination